Does the market know? Going concern opinion release and firm fundamentals - Huang, Jian; Yu, Han (International Journal of Accounting and Financial Reporting, 2019)
Using a significant auditing event-the going concern audit opinion-we investigate the market’s forecasting ability and the importance of firm fundamentals in predicting the going concern event. First, we find that the equity market signals the upcoming going concern announcement as early as 30 days in advance. Specifically, during the window of [-30, -1] leading up to the announcement, the excess returns to going concern firms are 9.98% worse than the matched distressed firms. Moreover, short sellers, a group of sophisticated investors, significantly increase their shorting activities during days before the release of the going concern opinions. Furthermore, we find that firm fundamentals, which are observable to the market, are significantly predictive to the issuances of going concern. These variables include a firm’s operating performance (return on assets and operating cash flows), equity market liquidity, stock momentum, and filing delay. Overall, our evidence supports the perception that the market can forecast the going concern opinion release and points out its possible channel as well.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/096-064-327-238-420, pop00331 tex.type: [object Object]
Keywords: dept.fin; peer-reviewed

Firm risk and proxy fights: Evidence from SOX - Chen, Fang; Huang, Jian; Yu, Han (Accounting and Finance Research, 2018)
The Sarbanes Oxley Act of 2002 (SOX) is documented to curb executive risk-taking and firm risk. Utilizing SOX as an exogenous shock on firm risk, we find that proxy fight threats are positively related to a firm’s total risk and idiosyncratic risk. Specifically, although firm risk generally decreases post-SOX, high proxy fight threats mitigate this change in firm risk. We also find that although firms adopt more conservative policies such as decreasing their leverage and payout post-SOX, these changes are mitigated by proxy fight threats. In sum, our findings indicate that proxy fights act as an external disciplinary mechanism, encourage executive risk-taking, and increase firm risk.
0 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.fin; peer-reviewed

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
1 citations (Crossref) [2023-10-31] tex.ids: chenIntraindustryEffectsProxy2020, lens.org/134-505-396-626-539 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85070373506 tex.type: [object Object] type: Article
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed

External vs. In-House Advising Service: Evidence from the Financial Industry Acquisitions - Huang, Jian; Yu, Han; Zhang, Zhen (Journal of Risk and Financial Management, 2023)
This study analyzes the wealth impact on M&A deals when the acquirers in the financial industry utilize external versus in-house advising services. A quasi-natural observatory setting is applied to investigate the costs and benefits of retaining a financial advisor. Based on agency theory, information asymmetry and conflict of interest both exist in the setting of M&A deals when acquirers use advisory services. We first find that almost 40% of financial acquirers are more likely to use in-house advising services, the frequency of which is significantly higher than that of non-financial acquisitions previously documented. Further, we find that in certain complex deals of greater information asymmetry, the frequency of retaining advisory services in-house is even higher. This finding suggests that for financial acquirers who possess expertise in the M&A market, the concern of conflict of interests (i.e., misaligned incentives) between the acquirers and their advisors are more salient than the concern of information asymmetry. More importantly, using the two-stage regressions method controlling the endogeneity of the choice between in-house versus external advisory services, this study finds that the three-day abnormal returns around the acquisition announcements are 4.5% higher for the acquirers retaining in-house advisory services, 18.7% higher for the corresponding target, and the combined merger gains are 2.2% higher. Overall, our findings provide direct evidence of the agency cost when an external advisor is hired and document the incremental values that the financial acquirers’ in-house advisory services may create.
0 citations (Crossref) [2023-10-31] Number: 2
Keywords: agency costs; dept.fin; external advisors; financial industry; in-house advisors; information asymmetry; peer-reviewed

Short selling prior to going concern disclosures - Huang, Jian; Wang, Lei; Yu, Han; Zhang, Zhen (Accounting and Business Research, 2020)
We provide insights into how the market processes going concern audit opinions based on the trading of some well-documented sophisticated investors–short sellers. We find that abnormal short selling increases significantly upon impending going concern disclosures. While prior literature attributed much of short selling around some corporate events to private information, we find evidence that pre-going-concern announcement short selling reflects both privately informed trading and processing of public information by short sellers. Further, a negative relation between pre-announcement short selling and post-announcement short-term stock returns exists for stocks with less short sale constraints. We also find moderate evidence associating short selling with subsequent bankruptcy to some extent. Overall, these results suggest that short sellers front run going concern announcements based on private information and fundamentals, although trading constraints prevent them fully impounding the severity of negative information in the short run, providing a partial explanation for the long-run price drift post-going concern. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
1 citations (Crossref) [2023-10-31] tex.ids: huangShortSellingPrior2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097052844 type: Article
Keywords: dept.fin; peer-reviewed

In-house deals: Agency and information asymmetry perspectives - Chen, Fang; Huang, Jian; Ma, Minghui; Yu, Han (Corporate Ownership and Control, 2021)
1 citations (Crossref) [2023-10-31]
Keywords: dept.fin; peer-reviewed